1999
DOI: 10.1021/jf9806356
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Maltodextrins and Antistaling Enzymes on the Differential Scanning Calorimetry Staling Endotherm of Baked Bread Doughs

Abstract: Different concentrations (1.2-3.6%) of maltodextrin preparations with average degrees of polymerization (DP) varying between 4 and 66 reduced the differential scanning calorimetry (DSC) staling endotherm in baked and stored (7 days, 23 degrees C) bread doughs from 3.4 mJ/mg to values within a 3.0-1.9 mJ/mg range. Commercial enzymes used in industrial practice as antistaling agents for bread also reduced amylopectin retrogradation. This suggested that the maltodextrins used are promising antistaling components … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
6

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 15 publications
2
34
0
6
Order By: Relevance
“…DSC /'esults Table 7 reported (Defloor & Delcour, 1999). However, why the addition of lipase alone increased the gelatinization enthalpy is still unknown at present.…”
Section: 63hmentioning
confidence: 98%
“…DSC /'esults Table 7 reported (Defloor & Delcour, 1999). However, why the addition of lipase alone increased the gelatinization enthalpy is still unknown at present.…”
Section: 63hmentioning
confidence: 98%
“…The anti-staling action of amylases has been attributed to the modified retrogradation behaviour of the hydrolysed starch [72][73][74]. Yet, other researchers ascribe the effect to the interference of the low molecular weight dextrins with starch-starch and/or gluten-starch interactions [74][75][76].…”
Section: Amylases and Other Starch-converting Enzymesmentioning
confidence: 99%
“…Chinachoti, Kim-Shin, Mari, and Lo (1991) reported that gelatinization temperature of wheat starch increased as the concentration of sucrose solution increased at more than 20% (as a starch basis). Defloor and Delcour (1999) studied the gelatinization properties of dough added several maltodextrins that have various degree of polymerization (DP), and reported that no significant difference was detected on the thermogram.…”
Section: Gelatinization Properties Of Dough Substituted With Various mentioning
confidence: 99%